Production of fiber hydrolysate from bamboo shoot with antioxidative properties by enzymatic hydrolysis - Karnjanapratum, Supatra; Kaewthong, Pensiri; Takeungwongtrakul, Sirima; Sae-Leaw, Thanasak; Hong, Jeong Hwa; Nalinanon, Sitthipong (My University, 2019)
Bamboo shoots possess a rich source of dietary fiber for Asian countries as well as Thailand, which give various beneficial physiological effects for human beings. Dietary fibers in soluble form could provide better texture and would be easier to apply in food products. This study aimed to prepare fiber hydrolysate with high solubility and antioxidant activity from bamboo (Bambusa vulgaris) shoot. The fiber hydrolysate from bamboo shoot (FHBS) was prepared by stepwise enzymatic hydrolysis including amylase (1%, w/w), cellulase (1, 2, 3%, w/w) and papain (1%, w/w). The released fiber yield of FHBS increased with increasing cellulose levels in dose dependent manner (P≤0.05). It was found that the process with 1% (w/w) amylase for 1 h and 3% (w/w) cellulase for 3 h followed by 1% (w/w) papain for 1 h at 50 ºC, rendered the highest released fiber yield (92.10±1.10%). The resultant FHBS contained 5.76±0.21 % of total dietary fiber with total sugar and reducing sugar contents of 1431.22±46.01 and 918.91±10.57 mg/g solid, respectively. The FHBS exhibited antioxidant activities including ABTS radical scavenging activities (ABTS), DPPH radical scavenging activities (DPPH), ferric reducing antioxidant power (FRAP) and oxygen radical absorbance capacity (ORAC). Therefore, FHBS with antioxidant activities could be effectively prepared by using enzymatic hydrolysis and suitable to apply in the fiber fortified products.
Keywords: Antioxidative properties; Bamboo shoot; Enzymatic hydrolysis; Fiber hydrolysate